Online Tax System and Tax Compliance by Small and Medium Enterprises: Case of Kitui County in Kenya - Mwangangi, Alex Kyalo; Memba, Florence Memba (Journal of Accounting, 2022)
Purpose: Technology has significantly impacted the efficiency of conducting business, among them, the digitalization of tax functions, which has led to the creation of operational efficiencies in terms of filing tax returns. The purpose of this research is to evaluate the effect of online tax system on tax compliance in Kitui County's SMEs. Specifically, the study focused on effect of online tax filling and online taxpayer registration on tax compliance in Kitui County. Methodology: This research was hinged on theory of Technological Acceptance Model, Diffusion of Innovation Theory and Theory of planned behavior. A descriptive research design was used in this study. The owners of the 442 small and medium businesses in Kitui County was the study's unit of analysis. A sample population of 206 is determined using the stratified proportionate random sampling technique. Self-administered questionnaires were used to collect primary data. The Statistical Package for Social Sciences was used to examine the data (SPSS Version 25.0). For all quantitative variables, descriptive statistics such as frequencies, percentages, average score, and standard deviation was computed after data cleaning, which includes checking for entry mistakes. The information was presented in tables and graphs. The relationships between the independent and dependent variables were established using multiple regression analysis. Findings: The study concluded that a unit increase in online tax registration leads to 0.807 increase in tax compliance by small and medium enterprises in Kitui County. The study revealed that a unit change in online tax filing leads to 0.731 change in tax compliance by small and medium enterprises in Kitui County. Unique Contribution to Theory, Practice and Policy: The study concludes that the KRA officials in Kitui county should conduct awareness programs among SMEs regarding the importance of online tax registration. The study informs policy as it seeks to help Kenya Revenue Authority in using effective measures to mobilize and motivate small tax payers to register online for turnover tax, value added tax among other taxes in order to increase tax compliance.